Laparoscopic radical lymph node dissection for advanced colon cancer close to the hepatic flexure. Issue 1 (12th August 2016) - Uematsu, Dai; Akiyama, Gaku; Sugihara, Takehiko; Magishi, Akiko; Yamaguchi, Takuya; Sano, Takayuki
Abstract: Introduction: Complete mesocolic excision is currently recognized as a standard procedure for colon cancer. Gastroepiploic, infrapyloric, and superficial pancreatic head lymph node metastases in the gastrocolic ligament have been reported for colon cancer close to the hepatic flexure. We sought to investigate metastases in the gastrocolic ligament in colon cancer close to the hepatic flexure. Methods: This was a single‐center retrospective study. All patients with T2 or deeper invasive colon cancer in the relevant tumor location who underwent laparoscopic right hemicolectomy or extended right hemicolectomy at our institution between 1 April 2011 and 31 March 2015 were included. Results: Lymph node dissection in the gastrocolic ligament was performed in 35 cases. Complications occurred in 11 patients (31%) and were grades I and II according to the Clavien–Dindo classification. Lymph node metastases in the gastrocolic ligament were found in only three patients (9%). Each metastasis was larger than 9 mm. Conclusions: Metastases in the gastrocolic ligament occurred in 9% of patients with T2 or deeper invasive colon cancer close to the hepatic flexure. Laparoscopy was feasible and useful during gastrocolic ligament resection. This study included a small sample and lacked an extended follow‐up. Further studies are needed to determine the clinical relevance of this finding, particularly in terms of recurrence and long‐term survival.